2020
DOI: 10.1016/j.euroneuro.2017.11.012
|View full text |Cite
|
Sign up to set email alerts
|

RBFOX1, encoding a splicing regulator, is a candidate gene for aggressive behavior

Abstract: The RBFOX1 gene (or A2BP1) encodes a splicing factor important for neuronal development that has been related to autism spectrum disorder and other neurodevelopmental phenotypes. Evidence from complementary sources suggests that this gene contributes to aggressive behavior. Suggestive associations with RBFOX1 have been identified in genome-wide association studies (GWAS) of anger, conduct disorder, and aggressive behavior. Nominal association signals in RBFOX1 were also found in an epigenome-wide association s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 95 publications
(101 reference statements)
0
36
0
Order By: Relevance
“…Interestingly, the protein encoded by RBFOX1 regulates the expression of 15 of the top 40 ranked genes (the probability of this event is p=3.4e-05) 70 . Convergent data from GWAS, neuroimaging genetics, epigenetics, gene expression and animal models supports RBFOX1 as a strong candidate for aggression 57 . Furthermore, all 40 genes are highly connected in three functional networks ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Interestingly, the protein encoded by RBFOX1 regulates the expression of 15 of the top 40 ranked genes (the probability of this event is p=3.4e-05) 70 . Convergent data from GWAS, neuroimaging genetics, epigenetics, gene expression and animal models supports RBFOX1 as a strong candidate for aggression 57 . Furthermore, all 40 genes are highly connected in three functional networks ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 96%
“…NFKB1 is a transcription factor involved in regulating responses of neurons to activation of different signaling pathways in a variety of physiological and pathological conditions 55 . RBFOX1 is a splicing factor implicated in many neurodevelopmental and psychiatric disorders and several evidences have highlighted this gene as a candidate for aggression 56 , 57 . WDR62 is a centrosomal and nuclear protein linked to autosomal recessive microcephaly 58 , 59 .…”
Section: Discussionmentioning
confidence: 99%
“…4b). Animal models and association studies have implicated RBFOX1 in aggressive behaviors, a trait observed in several of the disorders in our analysis (Fernandez-Castillo et al, 2017).…”
Section: Cross-disorder Meta-analysis Identifies 109 Pleiotropic Locimentioning
confidence: 90%
“…4b). Animal models and association studies have implicated RBFOX1 in aggressive behaviors, a trait observed in several of the disorders in our analysis (Fernandez-Castillo et al, 2017).Of the 109 pleiotropic loci, 76 were identified in the GWAS of individual disorders, while the remaining 33 are novel. The most pleiotropic among these novel loci was a region downstream of NOX4 (NADPH Oxidase 4) that was associated with SCZ, BIP, MD, ASD, and AN (rs117956829; Pmeta = 1.82 x 10 -9 ; Fig.…”
mentioning
confidence: 95%
“…(62–65) Animal models have shown that RBFOX1 is involved in mouse corticogenesis and aggressive behaviours. (62,64,66,67) POLR3C is included in a well-known small CNV located at 1q21.1, which contributes to a broad spectrum of phenotypes in addition to ADHD, including morphological features and autism spectrum disorders (ASD). (68,69) Genes listed in Table 1 may be viewed as having, individually, the highest credibility as ADHD candidate genes.…”
Section: Discussionmentioning
confidence: 99%